The Grid: BluePrint for a New Computing Infrastructure - Foster (Ian) ("17-A / 1, Main Ring RoadLajpat Nagar IV,New Delhi,New Delhi,India-110 024", 2006)
Grid ; Computing Infrastructure
22.5
Keywords: Grid ; Computing Infrastructure